2015
DOI: 10.14814/phy2.12651
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia reduces placental mTOR activation in a hypoxia-induced model of intrauterine growth restriction (IUGR)

Abstract: Mammalian target of rapamycin (mTOR) is a protein that regulates cell growth in response to altered nutrient and growth factor availability. Our objective was to assess activated mTOR and its intracellular intermediates p70, and 4EBP1 in placental and invasive trophoblast cells in a hypoxia‐induced model of intrauterine growth restriction (IUGR) in rats. Rats were treated with hypoxia (9%) for 4 days. Placental and fetal weights, as well as conceptus numbers were recorded at the time of necropsy. Immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…2). Studies of human pregnancy at high altitude and in several animal models of maternal exposure to chronic hypoxia have confirmed that gestational hypoxia leads to significant FGR [54][55][56][57] (Fig. 2).…”
Section: Effects Of Maternal Hypoxia On the Fetoplacental Unitmentioning
confidence: 79%
“…2). Studies of human pregnancy at high altitude and in several animal models of maternal exposure to chronic hypoxia have confirmed that gestational hypoxia leads to significant FGR [54][55][56][57] (Fig. 2).…”
Section: Effects Of Maternal Hypoxia On the Fetoplacental Unitmentioning
confidence: 79%
“…This can be attributed to an HPX-induced increase in placenta tissue volume [ 36 ] and an increase in both blood spaces and vessel diameters in the labyrinth. Others reported increased [ 37 , 38 ], decreased [ 39 ], and no change [ 36 , 40 ] in placental weight with HPX, identifying differences in hypoxic severity, timing of gestation, and animal species. Despite the increased placental weight, fetal body weight is decreased compared to their NMX controls, clearly indicating an inefficient placenta.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced oxidative stress leads to abnormal endoplasmic reticular (ER) function, resulting in trophoblast autophagy, autophagic vacuole formation and cellular apoptosis. These processes are associated with fetal growth restriction and are particularly more pronounced when trophoblasts are exposed to reduced oxygen tensions or nutrientdepleted environments (Curtis et al 2013, Kimball et al 2015. Endoplasmic stress and protein synthesis blockage have also been demonstrated in women living at high altitudes, exposed to chronic hypoxia (Yung et al 2012a).…”
Section: Er Stress/autophagy/apoptosismentioning
confidence: 99%